Assessing complex interactions between human and agro-ecosystem using satellite information. A case study in Katuk Odeyo, Western Kenya. - Mohd Noor, M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The objective of this study is to integrate socioeconomic, biophysical, and remote-sensing information to enhance the understanding of climate change, agriculture and food security within and between CCAFS sites. The purpose is to assess the agricultural production system in the CCAFS site Katuk Odeyo, Nyando (Western Kenya) to explore potential indicators that can be long-term monitored. Ecosystem health determines energy supply and demand by sustaining the productive capacity of the landscape. The study uses a pixel-based RapidEye satellite image classification and assessment of agroecosystem health (for agricultural practices and landscape health relations) to characterise Katuk Odeyo into four functional agro-zones: highly intensive agro-zone condition (IAC), good agricultural condition (GAC), potential agricultural condition (PAC), and semi agricultural condition (SAC).